Implementasi UU No. 40 Tahun 2004 Tentang Jaminan Sosial Nasional Terhadap Ketenagakerjaan Di Indonesia - Divanadrata, Alifaini; Santoso, Imam Budi (Jurnal Bedah Hukum, 2024)
This research aims to find out the value and advantage or self-employed employment and the legal implications of self-employed employment. Based on main legal material, legal principles and laws and regulations related to this research includes the self-employed employment. In the discussion in this research related to the Law of the Republic of Indonesia Number 40 of 2004 concerning Social Security for Employment. How is the government’s efforts in the social security program, how do workers get their rights in case of accidents or work mistakes, how do workers resigned or being fired and many else in Law of The Republic of Indonesia No. 40 of 2004 will be explained in this journal.